Occupational disease of health sector workers due to COVID-19 - Sánchez Ortega, Veneranda (2020)
Faced with the pressing situation that developed the viral disease better known as COVID-19, it served to highlight the lack of labor regulation in Mexico as an occupational disease for providers of services in the Health Sector. Method: Qualitative Research, through the analysis of scientific publications, which address the issue worldwide, the issue of contagion by Covid-19 in health care personnel. Results: The investigations that deal with the issue of Covid-19 and the personnel of the health sector, focus on the mental situation of the worker, being counted the investigations that deal in depth with the legal and labor situation of the workers in the health service. Conclusion: The lack of regulation of Covid-19 disease, as an occupational disease in the table of occupational diseases indicated in article 513 of the Federal Labor Law, leaves workers in the Health Sector unprotected.